1979
DOI: 10.1055/s-0028-1103931
|View full text |Cite
|
Sign up to set email alerts
|

Haarwachstum, Leberwerte und Lichtempfindlichkeit unter oraler Retinoid-Therapie bei Psoriasis

Abstract: In a multicentre, cooperative study into the treatment of extensive psoriasis with a new aromatic retinoid (Ro 10--9359) trichogram, liver function tests and the light erythema threshold were investigated. In some of the patients hair loss occurred, usually in the fifth to eighth week after a total dose of 1.9 g retinoid. In all cases this improved an average of six weeks after dose reduction or cessation of treatment. The trichogram in 27 patients showed a diffuse toxic hair loss. In 70% the effluvium was tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…The acute changes in the liver could be caused by Tigason although a multicenter trial including 291 patients showed only few abnormal S-GPT values [3]. A few well-doc umented cases of toxic hepatitis due to Tiga son have been reported previously [1], In our case, it is difficult to place the re sponsibility for the severe toxic hepatitis on either drug alone.…”
Section: Discussioncontrasting
confidence: 41%
“…The acute changes in the liver could be caused by Tigason although a multicenter trial including 291 patients showed only few abnormal S-GPT values [3]. A few well-doc umented cases of toxic hepatitis due to Tiga son have been reported previously [1], In our case, it is difficult to place the re sponsibility for the severe toxic hepatitis on either drug alone.…”
Section: Discussioncontrasting
confidence: 41%
“…It ceases after 6-8 weeks if treatment is discontinued. Hair root evaluation showed a telogen effluvium in 70% of cases, whereas in 22% of cases telogen and dystrophic anagen roots were found (Mahrle et al, 1979).…”
Section: Side Effectsmentioning
confidence: 96%
“…These RXR receptors are speculated to play a role in new hair growth [ 9 ]. Etretinate may cause accelerated hair growth, dose-dependent telogen effluvium, and, at a high dose, hair loss that may be associated with dystrophy of hair roots [ 8 ]. It is speculative whether the affected hairs have regrown in follicles from which hairs have previously been lost.…”
Section: Discussionmentioning
confidence: 99%